A new method for the simultaneous enhancement of methane yield and reduction of hydrogen sulfide production in the anaerobic digestion of waste activated sludge. (November 2017) - Dai, Xiaohu; Hu, Chongliang; Zhang, Dong; Chen, Yinguang
Graphical abstract: Highlights: An approach was used to enhance the CH4 yield while decreasing the H2 S production. Characteristic APS reductase and sulfite reductase were detected in this study. Alkaline fermentation had an adverse impact on the abundance of SRB. Alkaline fermentation made the acetotrophic methanogens more dominant. Abstract: The biogas generated from anaerobic digestion (AD) also includes undesirable by-product such as hydrogen sulfide (H2 S), which must be removed before the biogas can be used as a clean energy source. Therefore, it is necessary to find an appropriate strategy to simultaneously enhance the methane yield and reduce H2 S production. An efficient strategy—pretreating sludge at pH 10 for 8 d and adjusting the system at neutral pH to produce methane for 20 d—is reported for the synchronous enhancement of methane production and reduction of H2 S production during AD. The experimental results showed that the cumulative methane yield was 861.2 ± 6.1 mL/g volatile solids (VS) of sludge pretreated at pH 10 in semi-continuous stirred anaerobic reactors for 84 d, an increase of 49.6% over the yield in the control. Meanwhile, the cumulative production of H2 S was 144.1 × 10 −4  mL/g VS, 54.2% lower than that in the control.